The Political Economy of Energy Resources Between China and ASEAN States: Opportunity and Challenge. Issue 6 (1st November 2016) - Zhao, Siyang; Zhang, Zhenjiang
Abstract : This article deals with the energy resources cooperation between China and ASEAN countries from the perspective of political economy. The first part presents the foundations of the China-ASEAN energy cooperation, where economic comparative advantages exist between them. The second part briefly reviews the energy trade, investment, exploration, and transportation cooperation between China and each ASEAN country, and the regional and international institutions for ASEAN-China energy cooperation. The third part talks about challenges and problems including South China Sea disputes, perception of China's rise, and some ASEAN countries domestic energy policies and instabilities. In the last part, some policy suggestions are put forth for promoting China-ASEAN energy cooperation.